ANALISIS KETERLAMBATAN PROYEK KONSTRUKSI JALAN YANG MENGAKIBATKAN PUTUS KONTRAK DI KEPULAUAN MENTAWAI - Asril, Asril; Anif, Bahrul; Wardi, Wardi (SIGMA TEKNIKA, 2025)
In the Mentawai Islands Regency, West Sumatra Province, Indonesia, during the 2019–2024 period, five road construction projects with contract values exceeding five billion rupiah (non-small qualified contractors) experienced critical delays that resulted in contract termination. The study aims to identify the factors causing delays in road construction projects that resulted in contract termination in the Mentawai Islands Regency, as well as to analyze the most influential dominant factors. The research method used a quantitative approach with a questionnaire instrument distributed to 127 respondents consisting of owners, consultants, and contractors. The sampling technique was purposive sampling, while data analysis was carried out using SPSS software with multivariate statistical methods. The results of the study indicate that there are ten main factors that influence delays in road construction projects resulting in contract termination, namely managerial factors (11.087%), labor (9.164%), equipment (8.903%), supply chain management (7.953%), financial (7.505%), design (7.370%), weather and natural disasters (6.494%), geography and environment (5.128%), procurement of materials (4.506%), and payment (4.107%). The dominant factor causing delays in road construction projects resulting in contract termination in the Mentawai Islands is managerial factors with a contribution of 11.087%.